Penerapan Terapi Back Massage pada Nyeri Lansia Penderita Rematik di Puskesmas Kaliwungu - Rintia Aryandani; Hermawati Hermawati (Lembaga Pengembangan Kinerja Dosen, 2024)
Background: Indonesia is included in the category of rheumatism sufferers which is quite high, namely 6.3% in the world of the high rate of rheumatism in indonesia. if it is not treated, it will cause swelling and stiffness in the sufferer's joints, resulting in discomfort. for this reason, efforts are needed to control rheumatism. one of the rheumatism therapies is doing back massage. back massage is a technique for giving massage to the back with slow rubbing which provides a feeling of comfort and relaxation to the body. objective: to determine the intensity of the pain scale before and after giving back massage therapy and to see the effect of giving back massage therapy on pain in rheumatism sufferers. method: this type of research uses descriptive research methods and by observing 2 respondents with a history of rheumatism and who were given the implementation of back massage therapy. results: there was a decrease in the intensity of rheumatic pain after giving therapy on Mr. S from a scale of 5 to 2 and in Mrs. G from a pain scale of 6 to a pain scale of 2. Conclusion: there is an effect of giving back massage therapy on pain in rheumatism sufferers.